Al-Madrasah al-Baṣrīyah li-l-Naḥw al-‘Arabī - Ali Burhan (ALSINATUNA, 2016)
Mazhab of Basra is part of ideologies in nahw. It is the first embryo of traditional linguistics throughout the history. In this stage, there were many figures of nahw who developed the basic of nahw. This article provides the readers an illustration of geography of Basra as well as its history. In addition, it also provides the characteristics of the Islamic schools in building the basic principles of nahw and acquaints its figures of nahw as well as their best creations.